(untitled) (Eduscotech, 2022)
The problem in this study is the low level of creative thinking ability of fourth grade students at SDN Mranggen 3. This study aims to analyze the effect of the application of the Problem Based Learning learning model on students’ creative thinking abilities. Data collection techniques using tests. The research design uses Pre-Experimental Design with the type of One Group Pre test Post test Design. The population is 206 and the sample used is 22 students of class IV B, the sample is determined by the cluster random sampling technique. Data were analyzed using the t test. The results of this study show a significant effect of the application of the Problem Based Learning learning model on the creative thinking abilities of fourth grade students at SDN Mranggen 3 as indicated by the acquisition of t count (6.27) > t table (2.021).